327 Radical hysterectomy in early cervical cancer: characteristics and outcomes of a large-controlled european population. (4th December 2020) - Boria, Felix; Vazquez, Daniel; Castellano, Teresa; Chacon, Enrique; Mínguez, José Ángel; Cambeiro, Mauricio; Iscar, Teresa; Gonzalez-Martin, Antonio; Alcazar, Juan Luis; Chiva, Luis M
Abstract : Introduction/Background: Radical hysterectomy has been for years the primary treatment for early cervical cancer. Recently, a number of retrospective studies and a prospective randomized trial (LACC trial) revealed higher rates of recurrence and death in patients that underwent minimally invasive surgery. In Europe, we did not counted with large-contrasted data. We designed the SUCCOR study, a multicenter, observational cohort study with the primary goal of validating the results of the LACC trial in Europe. In this study we try to compile all the information obtained in the Succor study to offer a comprehensive picture of the characteristics and outcomes of the surgical treatment of early cervical cancer in this large European population. Methodology: Patients were eligible if they underwent a radical hysterectomy in a European Institution for stage IB1 cervical cancer (FIGO 2009), from January 1st, 2013 to December 31st, 2014. Results: From May 15th to November 15th, 2019, we received data from a total of 1272 patients. 116 patients were excluded. The final cohort was composed of 1156 patients. The median age of the studied population was 47.12 yo (10.8). 36.6% of patients had undergone a cone biopsy before the radical hysterectomy. The mean preoperative maximum diameter measured by magnetic resonance imaging was 19.58 mm (13.3). 633 (54%) radical hysterectomies were done by laparotomy and all the other 523 (46%) by minimally invasive surgery. Nerve sparing technique was carry out in 61.8% of cases. Only in 224 cases (19.4%) the sentinel lymph node biopsy was performed with a rate of bilateral identification of 79.7%. The average length of stay in the hospital was 6.72 days (4.2). The average number pelvic nodes retrieved was 25.51, showing 12.4% of patients, nodal metastasis. 510 patients (44.1) received any type of adjuvant therapy. Standard radiation plus braquitherapy were the most frequent used modality of adjuvant treatment (54.1 and 43.3% respectively) while concomitant chemoradiation was use in 34.1% of the cases. After a median follow up of 58 months, the 5-y disease free survival rate was 88.3% and the overall survival rate at 5-y was 94.9%. Conclusion: In this study we have collected the most extensive amount of information ever obtained on radical hysterectomy for cervical cancer in our continent. Even though it is a retrospective registry, the meticulous design of the inclusion and exclusion criteria offers a high level of accuracy when evaluating the surgical outcome of patients with cervical cancer after radical hysterectomy. Disclosures: All authors contributed to writing the manuscript and read and approved the final manuscript. The authors declare no conflict of interest.